Nurturing Moderate Islam: Strategic Da’wah Communication in The Digital Era for Generation Z - Choirin, Muhammad; Dwijayanto, Arik; Yumna, Laila; Muaz, Yusuf Ahmed (International Journal Ihya' 'Ulum al-Din, 2024)
Indonesia is a country rich in cultural diversity and home to the largest Muslim population in the world. The study explores the communication strategy of da’wah among Generation Z through digital media. Against diverse cultural influences, the research specifically aims to unravel the intricacies of employing digital media to convey moderate Islam's universal values. Qualitative methods such as interviews, observations, and documentation were employed to internalize the universal values of moderate Islam. What emerges from this exploration is the pivotal role of social media in crafting effective communication strategies. The findings, drawn from insights provided by five informants aged 21-24, underscore the significant role of social media in shaping effective communication strategies for proselytization and fostering the embrace of moderate Islamic values within Generation Z. This research not only contributes to the scholarly discourse on religious communication but also provides practical implications for those engaged in proselytizing efforts.